Clinical and imaging characteristics of early Parkinson's disease - Szewczyk-Krolikowski, K (2014)
Background . Pathological processes in Parkinson’s disease (PD) start long before the first symptoms appear and by the time the disease is clinically established the results of neurodegeneration may be irreversible. Efforts to prevent or stem disease progression need to start in early disease and good characterization and new markers of early PD are urgently needed. Objectives . This thesis aims to characterize early disease stages in three projects. Firstly, clinical features of PD within 3 years of diagnosis will be explored in an incident cohort of patients and controls, using a range of tools to cover the whole breadth of clinical presentation of PD. Secondly, functional imaging studies in PD published so far will be examined through a meta-analysis to identify the most robust functional imaging markers. Thirdly, a functional MRI resting-state study in early PD will be performed to identify reproducible differences between patients and matched control subjects. Results . The cohort analysis found that age was a strong predictor of disease severity, independent of disease duration, while gender was seen to affect disease severity depending on the body region. A meta-analysis of all published functional imaging studies across all disease stages showed abnormal activations in the Basal Ganglia but also in a wide range of motor and non-motor brain areas. Dopamine supplementation normalized activations in the Basal Ganglia and some other areas, while other circuits remained resistant to medication suggesting non-dopaminergic abnormality. In the resting-state study, the Basal Ganglia Network showed greatly reduced connectivity in early PD compared to controls, which normalized on administration of dopaminergic medication. Reduced BGN connectivity was also validated on a separate group of PD subjects achieving very good separation of patients from controls. Conclusions . The effect of gender and age on early presentation of PD has potential significance for early diagnosis and choice of outcome measures for clinical trials. Within the realm of imaging, traditional task-based fMRI studies fail to show a clear and reproducible pattern of activations making this method unfeasible for early diagnostic testing. In contrast, resting-state fMRI connectivity in the Basal Ganglia Network appears to be a promising and reliable method even in the early stages of PD. Clinical profiling and resting imaging changes offer avenues for developing future biomarkers in early PD.